Perlindungan Hukum bagi Perempuan Sebagai Korban Kekerasan Seksual dalam Hubungan Berpacaran (Studi Kasus Di DP3A Kota Semarang) - Theofany Renessa Dicta Natalie Putri; Wenny Megawati (JURNAL HUKUM PELITA, 2025)
This study examines the regulation and authority of the Medical Profession Disciplinary Council (MDPK) in enforcing professional discipline after the enactment of Law Number 17 of 2023 on Health, which repealed Law Number 29 of 2004 on Medical Practice. The research aims to analyze the legal framework governing MDPK, identify weaknesses in the regulation, and explore the urgency of reconstructing its authority to improve effectiveness in protecting patients and ensuring legal certainty for medical professionals. Using a normative juridical method with a statute, case, and conceptual approach, the study reveals that although the new regulation strengthens MDPK’s role in preventing over-criminalization of medical practitioners, it still suffers from regulatory gaps, overlapping authority, and implementation challenges. These include limited resources, lack of integrated information systems, and weak enforcement mechanisms. The findings propose a reconstruction model through the formulation of detailed technical regulations, granting semi-judicial status to MDPK, integrating it into a special medical court system, and developing an integrated case management system. Strengthening MDPK’s authority is essential to create a disciplinary enforcement system that is effective, transparent, and balanced between patient protection and the rights of medical practitioners